2020
DOI: 10.1186/s12969-020-00460-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health needs of adolescent and young adult women with pediatric rheumatic diseases

Abstract: Background: The purpose of this study was to identify reproductive health knowledge gaps and topics that concern adolescent and young adult (AYA) women with pediatric rheumatic diseases and their parents. Methods: Data collection occurred in two cohorts. In the first cohort, young women (15-20 years old) with pediatric-onset rheumatic conditions and their parents were recruited from a single, academic pediatric rheumatology center. In the second cohort, young women (18-25 years old) with pediatric-onset rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…12 Women with RD who are not actively pursuing pregnancy often have questions and concerns about contraception and the impact of their disease and medications on future fertility. 13 In addition to concerns about disease-and medication-related pregnancy risk, women with RD also express concerns about the heritability of their disease and the potential impact of their disease on their ability to care for themselves and their offspring. 13 It is likely that these factors contribute to the observed decreased family size in women with RD compared with women without these conditions.…”
Section: Family Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Women with RD who are not actively pursuing pregnancy often have questions and concerns about contraception and the impact of their disease and medications on future fertility. 13 In addition to concerns about disease-and medication-related pregnancy risk, women with RD also express concerns about the heritability of their disease and the potential impact of their disease on their ability to care for themselves and their offspring. 13 It is likely that these factors contribute to the observed decreased family size in women with RD compared with women without these conditions.…”
Section: Family Planningmentioning
confidence: 99%
“…13 In addition to concerns about disease-and medication-related pregnancy risk, women with RD also express concerns about the heritability of their disease and the potential impact of their disease on their ability to care for themselves and their offspring. 13 It is likely that these factors contribute to the observed decreased family size in women with RD compared with women without these conditions. 14,15 The 2020 American College of Rheumatology (ACR) reproductive health guideline recommends that rheumatologists treating women with RD of reproductive age discuss contraception and pregnancy plans at an early visit, periodically thereafter and whenever initiating teratogenic medications.…”
Section: Family Planningmentioning
confidence: 99%
“…Pregnant women with CID are concerned about the potential complications of pregnancy, as well as how their condition will affect their health and the health of the newborn. Concerns may have been raised about how the disease and its treatment will affect conception, the natural course of their pregnancy and childbirth, fetal development in the womb, child development after birth, and their ability to breastfeed and care for the child [5][6][7][8]. Previous research has found that women with active RA have higher rates of prematurity, preeclampsia, Cesarean delivery, and low birth weight infants, but women with well-controlled RA had pregnancy outcomes comparable to the general population [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey on the reproductive health needs of young and adolescent women suffering from pediatric RDs, both patients and parents expressed anxiety and fears about sexual life, pregnancy, contraception, and teratogenic medications. 10 They felt dissatisfaction in discussing these issues with rheumatologists and most often were referred to gynecologists to address them. Participants also reported differences of opinion and communication gaps between gynecologists and rheumatologists.…”
mentioning
confidence: 99%
“…Participants also reported differences of opinion and communication gaps between gynecologists and rheumatologists. 10 In another survey of women with RDs conducted across 6 developed nations (USA, UK, France, Germany, Italy, and Spain), between 30% and 55% of patients felt that their family planning and pregnancy-related concerns were not adequately addressed, and the majority (38%) of them felt that their gynecologist was the right care provider compared to rheumatologists (12%) to discuss these issues. 11 In another survey carried out in a single center in the United States, women with RDs preferred rheumatologists to initiate and rediscuss relevant aspects of sexual and reproductive health.…”
mentioning
confidence: 99%